The World Book dictionary. - World Book, Inc. (Chicago : World Book, 2011)
"A two-volume dictionary providing the meaning, spelling, and pronunciation of approximately 225,000 important and frequently used words and phrases in the English language. Features include illustrations, illustrative sentences, and a "Guide to Communications" covering punctuation and spelling tips; vocabulary lists by grade level; how to write effectively, and articles on special subjects"--Provided by publisher.
v. 1. A-K -- v. 2. L-Z.
Keywords: English language -- Dictionaries